Analysis of the Effect of Quality, Service Price and Satisfaction on Patients and Their Impact on Visits to Exclusive Dental Clinics in South Jakarta - Pamungkas, Aji Gempur; Suharko, Arief; Apriani, Desy; Jawahir; Nabila, Efa Ayu (APTISI Transactions on Management (ATM), 2023)
The low rate of repeat visits in exclusive dental clinics is an interesting problem to study. From the available data, as well as interviews with several owners of exclusive dental clinics in cities of Jakarta, Surabaya, Samarinda and Banjarmasin in Indonesia as well as from the initial observations at exclusive dental clinics in South Jakarta, we found that the rate of repeat visits for existing patients was much lower than for new patients. From previous studies, it was also found that patient visits to the dental clinic were very low. This was influenced by the low level of patient satisfaction with the dental clinic. Their article mentions that retaining existing patients who make repeat visits at health clinics is about five times more profitable than serving new patients. This study aims to determine the effect of quality, service price and patient satisfaction on patient loyalty which influences patients to make repeat visits to exclusive dental clinics in South Jakarta, Indonesia. The subjects of this study were patients who had made at least two visits to the same exclusive dental clinics in South Jakarta, as well as patients who had previously visited other exclusive dental clinics. In this study, the approach used is a quantitative approach, and the type of data used in this study uses quantitative data in the form of questionnaire tabulations and qualitative data in the form of the research object general observations. We collect primary data through respondents' answers to questionnaires and secondary data sources through information on the population of DKI Jakarta Selatan and the characteristics of the middle-upper economic community.